2021
DOI: 10.7150/ijms.60869
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor comparison in young patients presenting with acute coronary syndrome with atherosclerotic coronary artery disease vs. angiographically normal coronaries

Abstract: Background: Acute myocardial infarction is a relatively rare phenomenon in the young population. The incidence has nevertheless increased from years past, likely due to the presence of multiple risk factors from an increasingly younger age. Regardless of whether they have atherosclerotic coronary artery disease or normal coronary angiogram, young patients with risk factors for coronary artery disease (CAD), chest pain, and positive troponin, are initially treated in a similar fashion. Our goal was to shed ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Most of the cholesterol in the human body exists and is transported in the form of binding to lipoproteins and then transported to various parts of the body to play corresponding roles [ 3 ]. Studies have shown that the elevated contents of total cholesterol and LDL-C in the blood circulation are related to coronary atherosclerosis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the cholesterol in the human body exists and is transported in the form of binding to lipoproteins and then transported to various parts of the body to play corresponding roles [ 3 ]. Studies have shown that the elevated contents of total cholesterol and LDL-C in the blood circulation are related to coronary atherosclerosis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of great significance to accurately diagnose and evaluate the degree of coronary artery disease in cases with CHD. Although coronary angiography is the gold standard for evaluating the severity of CHD, it has inevitable limitations as a high-cost, invasive procedure [ 3 ]. Studies have found that dyslipidemia is closely connected with CHD, and low-density lipoprotein cholesterol (LDL-C) is a crucial hazardous factor for CHD [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among previous reports, current age of onset was 19 years old [ 3 , 6 - 9 ]. Age range between 19 and 29 years, and female sex were the only categories in which the number of patients with angiographically normal coronary arteries was higher than those with atherosclerotic CAD [ 3 ]. This could mean that patients with normal coronary anatomy may not be having an acute coronary syndrome (ACS) and could be presenting with symptoms due to other conditions, or out of fear that they may be experiencing an ACS [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute myocardial infarction (AMI) is the leading worldwide cause of cardiovascular events, and angina is commonly seen before AMI [1,2]. AMI is extremely rare in young patients: in one study in Poland, individuals under age 40 represented only 1-6% of all AMI patients [2][3][4][5]. The rate of incidence has increased over years past in younger patients (< 35 years old) compared to older patients, and the age of onset is gradually falling, likely due to the following multiple risk factors such as smoking, obese, hypertension, diabetes, hyperlipidemia (higher level of low-density lipoprotein-cholesterol (LDL-C)), higher level of uric acid, history of coronary artery disease, family history of premature AMI, non-obstructive coronary artery disease (CAD), and genetic polymorphisms related to blood coagulation, fibrinogen, homocysteine, being present [3,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation